PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS DAN LIKUIDITAS TERHADAP HARGA SAHAM PADA PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS DAN LIKUIDITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN JII (JAKARTA ISLAMIC IJII (JAKARTA ISLAMIC INDEX) DI BURSA EFEK INDONESIA - Timur Deni Krisnanto; Siti Alliyah (Universitas Slamet Riyadi, 2023)
This study aims to determine the effect of company size, profitability and liquidity on stock prices. For sampling, a purposive sampling technique was used, so that a sample of 12 JII companies were registered on the IDX for 2019-2021. This study uses the documentation method for data collection. The data analysis technique uses multiple linear regression analysis using SPSS version 19. The results of this study indicate that company size has a significant positive effect on stock prices. Profitability and liquidity have no effect on stock prices. Keywords: Company Size, Profitability, Liquidity, stock prices.